Metformin and propranolol combination prevents cancer progression and metastasis in different breast cancer models - Rico, Maria Jose (2017)
Discovery of new drugs for cancer treatment is an expensive and time-consuming process and the percentage of drugs reaching the clinic remains quite low. Drug repositioning refers to the identification and development of new uses for existing drugs and represents an alternative drug development strategy. In this work, we evaluated the antitumor effect of metronomic treatment with a combination of two repositioned drugs, metformin and propranolol, in triple negative breast cancer models. By in vitro studies with five different breast cancer derived cells, we observed that combined treatment decreased proliferation (P < 0.001), mitochondrial activity (P < 0.001), migration (P < 0.001) and invasion (P < 0.001). In vivo studies in immunocompetent mice confirmed the potential of this combination in reducing tumor growth (P < 0.001) and preventing metastasis (P < 0.05). Taken together our results suggest that metformin plus propranolol combined treatment might be beneficial for triple negative breast cancer control, with no symptoms of toxicity.